"5G+TSN+DT" Solutions for Digital Factory Key Issues of Networking, Precision, Automation and Digitalization. Issue 1 (1st January 2022) - Wang, Han; Li, Shaobin
Abstract: With advanced technologies of the Internet of Things (IoT) and Artificial Intelligence (AI) developing, key issues and challenges of networking, precision, automation and digitalization are arising for digital factory (DF) top designing and establishing. Advanced technologies of 5G, Time Sensitive Network (TSN) and Digital Twin (DT) provide new solutions for DT planning and operating. This study explores "5G+TSN +DT" practical solutions for DF designing and building, especially in the aspects of networking, precision, automation and digitalization, which is of great significance to understand the opportunities and challenges of DF industry development.